METHODS OF TEACHING A FOREIGN LANGUAGE TO CHILDREN AGED 5–6 THROUGH PLAY-BASED ACTIVITIES - Tashpulatova Sanobar Botirkulovna (Modern American Journals, 2026)
This article examines the pedagogical and methodological aspects of using play-based activities in teaching a foreign language to children aged 5–6. It substantiates the idea that play is the leading activity in preschool age and analyzes the effectiveness of play-based methods in the process of foreign language acquisition. The article describes methods of teaching a foreign language through didactic, movement-based, role-playing, musical, and dramatized games. In the conclusion, it is emphasized that play-based learning contributes to the development of children’s interest in a foreign language, speech activity, and communicative competence.
Keywords: Preschool education, foreign language, play activity, children aged 5–6, communicative competence, methodology.